2011
DOI: 10.1073/pnas.1105371108
|View full text |Cite
|
Sign up to set email alerts
|

Larger amygdala but no change in hippocampal volume in 10-year-old children exposed to maternal depressive symptomatology since birth

Abstract: Maternal separation and poor maternal care in animals have been shown to have important effects on the developing hippocampus and amygdala. In humans, children exposed to abuse/maltreatment or orphanage rearing do not present changes in hippocampal volumes. However, children reared in orphanages present enlarged amygdala volumes, suggesting that the amygdala may be particularly sensitive to severely disturbed (i.e., discontinous, neglectful) care in infancy. Maternal depressive symptomatology has been associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
226
2
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 343 publications
(253 citation statements)
references
References 65 publications
21
226
2
4
Order By: Relevance
“…A strength of the study is the laboratorybased assessment of maternal support during mildly stressful conditions, which very nicely mimics the challenges parents regularly face in child rearing. Maternal support at neither preschool nor school age emerged as a significant predictor of hippocampal volume, a finding consistent with cross-sectional studies showing that variations in maternal influences do not necessarily emerge as main effects in studies of neurodevelopment (2,3). However, the unique, longitudinal approach of Luby et al (1) reveals a compelling association between maternal support and hippocampal growth trajectories: hippocampal volume increased faster with age among subjects with higher levels of maternal support.…”
supporting
confidence: 72%
See 1 more Smart Citation
“…A strength of the study is the laboratorybased assessment of maternal support during mildly stressful conditions, which very nicely mimics the challenges parents regularly face in child rearing. Maternal support at neither preschool nor school age emerged as a significant predictor of hippocampal volume, a finding consistent with cross-sectional studies showing that variations in maternal influences do not necessarily emerge as main effects in studies of neurodevelopment (2,3). However, the unique, longitudinal approach of Luby et al (1) reveals a compelling association between maternal support and hippocampal growth trajectories: hippocampal volume increased faster with age among subjects with higher levels of maternal support.…”
supporting
confidence: 72%
“…Sensitive periods for environmental signals are also regionally specific, which may explain the discrepancies noted by Luby et al (1) between their findings and those of others groups. For example, the authors note that Lupien et al (3) reported MRI findings with similarly aged subjects (mid-childhood), showing an association between postnatal maternal depression and the volume of the amygdala, but not the hippocampus. However, there are prenatal maternal influences, including maternal mood on the amygdala but not hippocampal volume, which are sustained into late childhood (9,10).…”
Section: Sensitive Periodsmentioning
confidence: 99%
“…MRI and fMRI studies have indicated, for example, that exposure to harsh and unpredictable childhood conditions (e.g., parental neglect) is associated with greater volume and reactivity of the amygdala, a portion of the brain that is responsible for vigilance and emotional responsiveness to threat (e.g., Mehta et al 2009), and alteration of the prefrontal cortex, the area responsible for executive control (Hanson et al 2010;Wilson et al 2011). Other studies have reported that among adopted children, those adopted later have larger amygdala volume than those adopted earlier (Tottenham et al 2010), and that children continuously exposed to maternal depression show larger amygdala volume than those without such exposure (Lupien et al 2011). Importantly, the amygdala and prefrontal cortex, as well as their interconnection, are implicated in emotional regulation (e.g., Wager et al 2008), impulsivity (e.g., Kim and Lee 2011;Raine 2002), reactive aggression (Crowe and Blair 2008), and internalizing problems (Tottenham et al 2010).…”
Section: Anomalies That Challenged the Old View Of The Brainmentioning
confidence: 99%
“…No study, so far, has investigated the impact of FKBP5 on amygdala volume. However this issue may be crucial, given the facts that FKBP5 is expressed in the amygdala (Scharf et al 2011) and that amygdala volume is increased following stress (Buss et al 2012;Lupien et al 2011;Tottenham et al 2010).…”
Section: Introductionmentioning
confidence: 99%